Level of Depression, Criminogenic Cognition, Relapse Risk, and Quality of Life among Patients with Substance Use Disorders : Level of Depression, Criminogenic Cognition and QoL - Shahzadi, Mafia; Mahmood, Khalid (Pakistan Journal of Health Sciences, 2023)
Substance use disorders (SUDs) involve symptoms caused by using a substance that an individual continues taking despite its negative effects. Patients with opioid use disorder (OUD) and other substance use disorders (O-SUDs) experience psychosocial problems that affect their quality of life (QOL). Objective: To determine the difference in depression, criminogenic cognition, relapse risk, and quality of life between patients with OUD and O-SUDs. Methods: In this cross-sectional study, the sample was collected from different rehabilitation centres in Faisalabad and Lahore. A purposive sampling technique was used to collect data from individuals with OUD (150) and O-SUDs (150) with relapse conditions through Alcohol, Smoking, and Substance Involvement Screening Test (ASSIST), Criminogenic Cognition Scale (CCS), Patient Health Questionnaire-9 (PHQ-9), Relapse Risk Scale (RRS) and WHO Quality of Life (WQOL). The collected data were prepared for statistical analysis using SPSS, Version-26. Results: The finding shows a significant difference between patients with OUD and with O-SUDs on the variables of PHQ-9, short-term orientation, negative attitudes toward authority, notions of entitlement, failure to accept responsibility, insensitivity to the impact of crime, and criminogenic cognition. In addition, a significant difference was found between patients with OUD and with O-SUDs on anxiety problems, positive expectancies and compulsivity, abstinence violation effect, low self-efficacy, relapse risk and QOL. Conclusions: It is concluded that depressive symptoms, criminogenic cognition, relapse risk conditions, and quality of life were higher among patients with OUD than patients with O-SUDs.